Communiy-Acquired pneumonia in children : Burden of disease and quality of life - Rania Ramadan Mohamed Mohamed; Mohammed Abdelfatah Abdelmotey; Nadia Ahmed Amin Mostafa; Rehab Abdelhai Ahmed Abdelhai (Cairo : Rania Ramadan Mohamed Mohamed, 2013)
Pneumonia is one of the most common leading causes of death in children in all the age groups. Children with pneumonia may have a renge of symptoms depending on their age and the cause of the infection. The disease represents a burden on the child being a patient and a burden on the family in the form of physical, psychological, emotional, economical and social strains.
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Cytomegalovirus; Herpes simplex virus; Pneumonia